Exploring the Implementation of Problem Based Learning for Class XI Biology in Senior High School - Galingging, Prazna Ivanka; Arwita, Widya (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
This research explores the implementation of the Problem Based Learning (PBL) model in Biology learning for class XI students at SMAN 1 Medan. The research is motivated by the need for effective learning models that can enhance students’ critical thinking and problem-solving skills in accordance with the Merdeka Belajar curriculum. The aim of this study is to investigate how well the PBL model is applied in classroom learning and identify challenges during its implementation. Using a qualitative exploratory method with a case study approach, data were collected through classroom observations and questionnaires administered to four Biology teachers and 144 students from four selected classes. The findings reveal that while the initial stages of PBL such as student orientation to problems and organizing students to learn were carried out effectively, the later stages, particularly guiding investigations, developing presentations, and evaluating problem-solving, were not optimally implemented. Teachers tended to provide less guidance during investigations and lacked structured reflection activities. Questionnaire results indicated a positive perception from both teachers and students, although observations showed inconsistency in implementation. In conclusion, the PBL model was generally well-received but still requires improvements, especially in teacher facilitation and reflective practices, to maximize its impact on student learning outcomes.